ON THE ROLE OF THE STATUS OF LANGUAGE AND THE SPECIFICS OF ITS USE IN LEGAL SOURCES - Nasiba Zhurabekovna Niyazova; Saltanat Shaidulayevna Koshalieva (American Journals, 2023)
The article examines the issues of legal regulation of the language in various types of sources of law: international acts, regulatory legal acts. In each of these sources, the role of the language and the peculiarities of its use in certain legal relations are considered in detail. Also, the latest changes in the legislation of the Republic of Uzbekistan on the issue of increasing the status of the state language were taken into account.
Keywords: International acts, national legislation, discrimination, minorities, protection of rights, state language.